(untitled) (Teacher Education through Flexible Learning in Africa (TETFLE), 2021)
Formal Education in the 21st Century is focused on the development of learners’ skills and competencies essential to navigate the complexities and uncertainties of the age. Effective acquisition of these skills in the school is predicated on adequate provision of technological resources, adequate school infrastructure and continuous professional development of teachers for innovative instructional delivery. Therefore, this study was carried out to investigate the extent to which infrastructural provisions and continuous professional development of teachers in secondary schools in Nigeria support the development and acquisition of 21st Century teaching and learning skills. The study which adopted the impact of school infrastructure on learning by Barrett et al.as a conceptual framework, used descriptive survey design. Two self-constructed instruments were used to collect data from (20) selected secondary schools, (50) teachers and (200) students. Data were analysed using frequency count, percentage score, mean, and standard deviation. Findings showed that the schools visited lack infrastructural provisions, the teachers do not have the requisite skills and the students are not aware of any other means of learning different from the conventional styles offered by their teachers. Therefore, this study offered a two-prong approach of immediate provision of technological infrastructure for schools and the development of teachers’ professional skills through focused training targeted at enhancing their technological instructional delivery skills.